Site suitability for public park using analytic hierarchy process and geographic information system / Khalilah Hassan - Khalilah, Hassan (Universiti Teknologi MARA, Perak, 2017)
Optimal locations for public parks are significant issues in a town planning. The current distribution of public park in Kota Bharu, not reflect their current population densities. Therefore, Kota Bharu Municipal Council (MPKB) administration area was selected as the study area where the land suitability model was applied to determine the suitable area for public parks. This study was carried out using an Analytical Hierarchy Process (AHP) as a multi-criteria evaluation approach by integrating it with the Geographic Information System (GIS). The IDRISI GIS package was used to calculate the weights based on four alternative scenarios, (a) population density, (b) existing public parks, (c) industrial area and, (d) land availability. Based on the findings made in this research, suitable locations for future public park development is highly helpful in the future land use planning in Kota Bharu, Kelantan.